Analysis of the German Perinatal Survey of the Years 2007–2011 and Comparison with Data From 1995–1997: Maternal Characteristics - Scholz, R.; Voigt, M.; Schneider, K. T. M.; Rochow, N.; Hagenah, H.-P.; Hesse, V.; Straube, S. (Geburtshilfe und Frauenheilkunde, 2013)
Background and Aim: We have previously presented analyses of data obtained from the German Perinatal Survey for the years 1995–1997. Here we present an analysis of data from the years 2007–2011 and compare the data to the previous data from the 1990s. Material and Methods: For the years 1995–1997, the data on 1 815 318 singleton pregnancies were provided by the Chambers of Physicians of all the states of Germany except Baden-Württemberg. For the years 2007–2011, the data on 3 187 920 singleton pregnancies from the German Perinatal Survey (all states of Germany) were obtained from the AQUA Institute in Göttingen, Germany. SPSS was used for data analysis. Plausibility checks were performed on the data. Results: Mean maternal age has increased over the years, from 28.7 years in 1995 to 30.2 years in 2011. We observed a decrease in smoking. While not all cases included data on maternal smoking after the pregnancy was known, when the cases with data on smoking were analysed, in 1995–1997 23.5 % of pregnant women were smokers compared to 11.2 % smokers in 2007–2011. Maternal body mass index (BMI) also changed; 8.2 % of women were obese (BMI: 30–40 kg/m2), while 13.0 % were obese in 2011. In 1995, 0.6 % of women were morbidly obese (BMI ≥ 40 kg/m2) compared to 1.8 % of women in 2011. The mean maternal body weight at the time of the first obstetric consultation also increased from 65.9 kg in 1995 to 68.7 kg in 2011. Conclusions: While the decrease in the number of women smoking over time is clearly a positive development, increasing maternal age and obesity present challenges in clinical practice.
Keywords: German Perinatal Survey; smoking; maternal age; obesity; delivery statistics